A material calculation-driven composition design method for T-phase precipitation-strengthening Al-Mg-Zn alloy

The alloying elements are screened through material calculation-driven methods, promote T-phase precipitation, and design a new Al-Mg-Zn alloy system, which solves the problem of performance differences between traditional aluminum alloys in different structural parts, and achieves efficient alloy design and performance optimization.

CN119207674BActive Publication Date: 2025-03-18GRIMAT ENG INST CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411677960.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-18
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The strength and ductility of traditional commercial aluminum alloys in different structural parts lead to increased production difficulty and manufacturing costs, which cannot meet the needs of multi-purpose and sustainable development.

Method used

Using a material calculation-driven method, a new Al-Mg-Zn alloy system was designed by screening alloying elements to promote the number of T-phase precipitation, and a new alloy design idea and process was proposed.

Benefits of technology

Through material calculation simulation and experimental verification, the alloy design is accurately guided, repetitive experimental work is reduced, and R&D time and cost are saved, providing a theoretical basis for designing high-performance aluminum alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119207674B_ABST
    Figure CN119207674B_ABST
Patent Text Reader

Abstract

The present invention discloses a material calculation driven T-phase precipitation strengthening Al-Mg-Zn alloy composition design method, which belongs to the technical field of aluminum alloy material design and microstructure optimization. The method first establishes the Al-Mg-Zn alloy T-Mg 32 (Al, Zn) 49 The atomic structure model of the phase is obtained by using a special quasi-random structure method to generate an intrinsic T phase crystal structure model, and the model is optimized. Then, a doping alloying element model is constructed based on the initial model, and the energy index is further used to evaluate the stability of the doping elements at different sites, and the rationality of the screening results is judged in combination with the electronic structure analysis. Finally, the influence of alloying elements on the precipitation of T phase is quickly verified by experiments such as measuring the mechanical properties and microstructural characteristics of the alloy, thereby providing data support and optimization basis for the design of new aluminum alloys. This method can effectively quantify the influence of alloying elements on the precipitation of T phase, and can accelerate the experimental process, saving time and cost in the research and development of new materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a material calculation-driven T-phase precipitation strengthening Al-Mg-Zn alloy composition design method, belonging to the technical field of aluminum alloy material design and microstructure optimization. Background Art

[0002] With the rapid development of industrial technology, energy crisis and environmental problems are becoming increasingly prominent, and sustainable development has become a new trend in global development. The development of lightweight materials has become an effective way to save energy. Aluminum alloys play an irreplaceable role in the lightweight development of transportation, construction, industry and other fields due to their high specific strength, good ductility, easy recycling and lightweight properties. However, traditional commercial aluminum alloys are often high-performance alloys designed within a specific narrow application range. In actual applications, the differences in strength and ductility of different structural parts require different connection processes, which increases production difficulty and manufacturing costs and cannot meet today's needs.

[0003] In order to solve these limitations, it is urgent to introduce the cross alloy design concept for recycling and multi-purpose, and develop new alloys that combine the advantages of different commercial aluminum alloys. Among them, lightweight Al-Mg-Zn alloy is a low-density cross alloy with a composition range between 5xxx and 7xxx series. 32 (Al, Zn) 49 It has become a research hotspot due to its wide range of compositions, excellent high temperature mechanical properties, corrosion resistance and radiation resistance.

[0004] In lightweight Al-Mg-Zn alloy systems, T phase is the main aging precipitation strengthening phase, and its precipitation characteristics play an important role in the strength of the alloy. At present, some research reports have been published on the composition control and performance optimization of T-phase strengthened Al-Mg-Zn(-X) alloys, but the composition and precipitation behavior of T phase in different aluminum alloy systems are still unclear. Although material design methods driven by material calculation have been widely used in the field of energy materials, they are relatively less used in the design of metal materials. Summary of the invention

[0005] Based on the above prior art, in order to meet the design requirements of new alloys, the purpose of the present invention is to provide a material calculation-driven T-phase precipitation strengthening Al-Mg-Zn alloy composition design method. This method obtains a new Al-Mg-Zn alloy system by screening alloying elements to promote the amount of T-phase precipitation, thereby proposing a new alloy design idea and process. The present invention can accelerate the experimental process and save time and cost in the research and development of new materials by deeply combining material calculation and experimental methods.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] A material calculation-driven T-phase precipitation strengthening Al-Mg-Zn alloy composition design method comprises the following steps:

[0008] (1) Establish Al-Mg-Zn alloy T-Mg 32 (Al, Zn) 49 Phase atomic structure model:

[0009] Based on experimental and simulation literature, the basic crystal structure data of the precipitated phase was obtained, and the special quasi-random structure method (SQS) was used to generate the intrinsic T phase crystal structure data file with a specific Zn content. The file was converted into an intrinsic structure model through the vesta software, and the intrinsic structure model was optimized to obtain the optimized T phase structure data file (CONTCAR) and system energy E 0.

[0010] (2) Based on the initial model, a doping alloying element model is established, and then energy calculation and electronic structure analysis are performed to screen out potential alloying elements that promote the precipitation of T phase; the specific steps are as follows:

[0011] (i) Determine the screening range of alloying elements, and divide the optimized CONTCAR file according to different sites of the crystal structure. For different sites such as Al / Zn sites, use random numbers to determine the substitution position;

[0012] (ii) Select the doping element X and then use the Materials Visualizer module in Materials Studio to construct the crystal structure data file after the doping element replaces the initial element at the Mg site or Al / Zn site to form a structural model for each doping site;

[0013] (iii) optimizing the structural model of each doping site established in step (ii) to obtain the T-phase structural data file (CONTCAR) of doping element X and the corresponding doping system energy;

[0014] (iv) By comparing the energy indices, we can determine the stability of the doped elements at each site of the T phase. Combined with the analysis of the electronic bonding characteristics, we can further determine the rationality of the energy indices and screen out potential alloying elements that promote the precipitation of the T phase.

[0015] (3) Experimental verification: Design new alloy compositions based on the selected alloying elements to obtain the mechanical properties and microstructural characteristics of the alloy. Through experiments, quickly verify the promoting effect of these alloying elements on the T-phase precipitation behavior, provide a basis for the design of new aluminum alloys, and further optimize the alloy performance.

[0016] Furthermore, in the step (1), the intrinsic structure model is optimized by using a first principle calculation program VASP based on density functional theory.

[0017] Furthermore, in the step (1), the error of the optimized T-phase lattice constant compared with the experiment is less than 5%, and the Zn content in the intrinsic structure model is close to the experimental range.

[0018] Furthermore, in the step (iv), the energy indicator is substitution energy or Gibbs free energy.

[0019] Furthermore, in the step (iv), energy calculation is performed using a density functional theory-based calculation method to quantitatively describe the effect of alloying elements on T phase precipitation, which can also be achieved through techniques such as machine learning or artificial intelligence.

[0020] Furthermore, in step (3), the mechanical property of the alloy is hardness or strength.

[0021] The beneficial effects of the present invention are:

[0022] 1. The present invention proposes a design method based on alloying elements to promote T-phase precipitation through a material computational simulation method. Through the steps of crystal structure optimization, energy calculation, and electronic structure analysis proposed in the method of the present invention, the influence of alloying elements on T-phase precipitation behavior can be intuitively quantified. This method screens out potential alloying elements that promote T-phase precipitation through theoretical calculations, accurately guides alloy design, reduces a large amount of repetitive experimental work, and provides a theoretical basis for the design of high-performance aluminum alloys.

[0023] 2. The present invention designs a T-phase precipitation strengthening design process for aluminum alloys based on a combination of calculation and experiment, and uses the material calculation method to conduct an in-depth analysis of the promotion mechanism of T-phase precipitation. The promotion effect of alloying elements on T-phase precipitation is verified by experiments, which greatly simplifies the complexity of traditional experimental methods and saves R&D time and cost. This method provides a scientific theoretical basis and technical support for the composition design of new aluminum alloys, which helps to accelerate the R&D process of new materials.

[0024] 3. This process is not only applicable to calculation methods based on density functional theory, but can also be extended to technologies such as machine learning or artificial intelligence to screen alloying elements that promote T phase precipitation through indicators such as energy. Regardless of the calculation method used, this process can efficiently screen out potential alloying elements and combine them with experiments for further verification, thereby accelerating the design of new aluminum alloys.

[0025] 4. The present invention can be applied to the design and optimization of different alloy systems, expanding the research and development path of new aluminum alloy systems. By screening out alloying elements with industrial application potential, the present invention provides guidance for further optimizing the performance of aluminum alloys, especially in terms of mechanical properties, corrosion resistance, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Mg in Example 1 of the present invention 64 Al 42 Zn 54 Schematic diagram of the crystal structure.

[0027] Figure 2 Schematic diagram of the structure after the Al atom at the B site is replaced by the X element in Example 1 of the present invention.

[0028] Figure 3 1 is the aging hardening curve of different alloys at an aging temperature of 140° C. in Example 1 of the present invention.

[0029] Figure 4 The microstructure morphology of the alloy in the aged state in Example 1 of the present invention, wherein (a) is the microstructure morphology of the Al-8.5Mg-3Zn alloy in the aged state; (b) is the microstructure morphology of the Al-8.5Mg-2Zn-1Ga alloy in the aged state. DETAILED DESCRIPTION

[0030] The present invention is further described below through the accompanying drawings and specific implementation modes, but it is not intended to limit the protection scope of the present invention.

[0031] Example 1

[0032] Taking the alloying elements of the fourth period Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Ga and Ge as an example, the material calculation-driven T-phase precipitation strengthening Al-Mg-Zn alloy composition design method includes the following steps:

[0033] 1. Based on experimental literature, a special quasi-random structure method was used to generate T phase crystal structure data files with medium Zn content (33.8%). Figure 1 Mg 64 Al 42 Zn 54 The schematic diagram of the unit cell structure, the big black balls are Mg atoms, the big white balls are Al atoms, and the small white balls are Zn atoms. The file is converted into a crystal intrinsic structure model using the Vesta software, and the intrinsic structure model is optimized using the first-principles calculation program VASP based on density functional theory to obtain a stable structure data file (CONTCAR) and system energy E0. The lattice constant of the system is 1.42 nm, which is basically consistent with the experimental value of 1.41~1.46 nm; the concentration of Zn atoms in the precipitated phase is also within the observed range of Al-Mg-Zn alloys reported.

[0034] 2. Determine the screening range of alloying elements, and divide the optimized CONTCAR file according to different sites of the crystal structure. For different sites such as Al / Zn sites, use random numbers to determine the substitution position. For the T-phase crystal structure, it contains the B, C, and F sites occupied by Al / Zn atoms, and the D, E, G, and H sites occupied by Mg atoms, so 10 possible substitution situations need to be considered. For the substitution model of different sites, we use random numbers to determine the substitution position, such as the substitution structure model of the doping element X replacing the Al atom at the B site (see Figure 2 ), the small black ball is the position of atom X. Repeat the above steps for other sites.

[0035] 3. Use the Materials Visualizer module in Materials Studio software to construct the crystal structure data file after the doping element replaces the initial element, and form the structural model of each doping site. Optimize the established series of doping structure models to obtain the stable structure data file (CONTCAR) and corresponding doping system energy of different doped X element crystals.

[0036] 4. Using substitution energy as a standard, evaluate the effect of different alloying elements on T phase precipitation. The substitution energy formula is as follows:

[0037] ,

[0038] in μ X is the chemical potential of the solute element X atom in the aluminum matrix, μ i is the chemical potential of the replaced Al, Mg or Zn atoms in the aluminum matrix. The above data can be obtained by establishing an aluminum alloy solid solution atomic model using first-principles calculation software.

[0039] According to the formula, the substitution energy of different alloying elements for atoms at each site in the T phase can be calculated. The calculation results are shown in Table 1. The negative value sites have been bolded and underlined, indicating that it is thermodynamically favorable for element X to enter this site, and it is an element that promotes the precipitation of the T phase. Taking the Ca element as an example, by calculating the 10 possible results of Ca entering different sites of the T phase and replacing atoms at different sites, it can be determined that the Ca element is more inclined to enter the D, E, G and H sites to replace Mg atoms. In summary, Ca, Sc, Co, Ni, Cu, Ga and Ge are potential elements that promote the precipitation of the T phase in terms of thermodynamics.

[0040] Table 1 Substitution energy of alloying elements for atoms at each site in the T phase (unit: eV)

[0041]

[0042] 5. Taking Ga as an example to replace Al atoms in the C site of T phase, based on the first principle electronic structure analysis software, we compared the total bond strength between the site and the surrounding atoms before and after Ga substitution, as well as the change in bond strength between the site and the nearest neighbor atoms of different types. The bond strength is quantitatively represented by the bond order. The larger the value of the bond order, the stronger the chemical bond between the two atoms. The calculation results are shown in Table 2, where SBO is the total bond order.

[0043] Table 2 Comparison of bonding strength before and after Ga replaced Al atoms at C sites in T phase

[0044]

[0045] Through electronic structure analysis, it can be found that when Ga replaces the Al atom at the C site of the T phase, the surrounding bonding strength will be comprehensively enhanced, verifying the rationality of the energy index for the Ga screening results.

[0046] 6. Based on the alloying element Ga obtained by the previous material calculation and screening, two high-Mg aluminum alloy systems with different chemical compositions but the same total solute content were smelted. The specific compositions are Al-8.5Mg-3Zn and Al-8.5Mg-2Zn-1Ga (mass percentage). For these two alloys, appropriate heat treatment processes were designed and adopted respectively, and the aging hardening curves of different alloys at an aging temperature of 140°C were obtained (see Figure 3 ). With the extension of aging time, the hardness of both alloys gradually increases, and the hardness of Ga-containing alloy is greater. The microstructure of the two alloys after reaching the peak aging state was observed by transmission electron microscopy (TEM) (see Figure 4 (a) and Figure 4 (b)), it was found that the Ga-containing alloy showed a denser distribution of precipitate phase. This observation confirms the positive role of Ga element in promoting the formation of precipitate phase. Therefore, the Al-Mg-Zn-Ga alloy system shows significant potential as a high-performance alloy material, indicating that it has broad application prospects in improving the performance of aluminum alloys.

[0047] In summary, the technical solution of the present invention can efficiently identify alloying elements that promote the precipitation of T phase. This method significantly simplifies the exploration process of new alloy systems, helps to shorten the time cycle of new material development, and reduces R&D costs.

[0048] The above embodiments are only used to illustrate rather than limit the technical solutions of the present invention. Although the above embodiments describe the present invention in detail, relevant technical personnel in the field should understand that any equivalent transformations made using the contents of the present invention specification, or directly or indirectly applied in related technical fields, but any modifications and substitutions that do not depart from the spirit and scope of the present invention should be included in the protection scope of the present invention.

Claims

1. A material calculation driven T-phase precipitation strengthening Al-Mg-Zn alloy composition design method, characterized in that: The following steps are involved: (1) Establish Al-Mg-Zn alloy T-Mg 32 (Al, Zn) 49 Atomic structure model of phase: Based on experimental and simulation literature, the basic crystal structure data of the precipitated phase is obtained, and the intrinsic T phase crystal structure data file with a specific Zn content is generated using a special quasi-random structure method. The file is converted into an intrinsic structure model using the vesta software, and the intrinsic structure model is optimized to obtain the optimized T phase structure data file and system energy E 0; (2) Based on the initial model, a doping alloying element model is established, and then energy calculation and electronic structure analysis are performed to screen out potential alloying elements that promote the precipitation of T phase; the specific steps are as follows: (i) Determine the screening range of alloying elements, and divide the optimized T-phase structure data file according to different sites of the crystal structure. For the Al / Zn site, use random numbers to determine the substitution position; (ii) Select the doping element X and then use the Materials Visualizer module in Materials Studio to construct the crystal structure data file after the doping element replaces the initial element at the Mg site or Al / Zn site to form a structural model for each doping site; (iii) optimizing the structural model of each doping site established in step (ii) to obtain a T-phase structural data file of the doped element X and the corresponding doping system energy; (iv) judging the stability of the doping elements entering each site of the T phase by comparing the energy index, and further judging the rationality of the energy index by combining the analysis of the electronic bonding characteristics, and screening out the alloying elements that potentially promote the precipitation of the T phase, wherein the energy index is the substitution energy or the Gibbs free energy; (3) Experimental verification: Design new alloy compositions based on the selected alloying elements to obtain the mechanical properties and microstructural characteristics of the alloy. Through experiments, quickly verify the promoting effect of these alloying elements on the T-phase precipitation behavior, provide a basis for the design of new aluminum alloys, and further optimize the alloy performance.

2. The material calculation driven T-phase precipitation strengthening Al-Mg-Zn alloy composition design method according to claim 1, characterized in that: In the step (1), the intrinsic structure model is optimized by using the first principle calculation program VASP based on density functional theory.

3. The material calculation driven T-phase precipitation strengthening Al-Mg-Zn alloy composition design method according to claim 1 or 2, characterized in that: In the step (1), the error of the optimized T phase lattice constant compared with the experiment is less than 5%, and the Zn content in the intrinsic structure model is close to the experimental range.

4. The material calculation driven T-phase precipitation strengthening Al-Mg-Zn alloy composition design method according to claim 1, characterized in that: In the step (iv), energy calculation is performed using a density functional theory-based calculation method to quantitatively describe the effect of alloying elements on T phase precipitation.

5. The material calculation driven T-phase precipitation strengthening Al-Mg-Zn alloy composition design method according to claim 1, characterized in that: In the step (3), the mechanical property of the alloy is hardness or strength.

Citation Information

Patent Citations

  • Al-Mg-Zn-Cu alloy design method based on ICME

    CN118360508A

  • Ti2AlNb alloy component optimization method based on first principle and phase diagram calculation

    CN118737332A